2021
DOI: 10.3389/fmolb.2021.720020
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of HDAC Family Identifies HDAC1 as a Prognostic and Immune Infiltration Indicator and HDAC1-Related Signature for Prognosis in Glioma

Abstract: Background: The histone deacetylase (HDAC) family limited accessibility to chromatin containing tumor suppressor genes by removing acetyl groups, which was deemed a path for tumorigenesis. Considering glioma remained one of the most common brain cancers with a dichotomy prognosis and limited therapy responses, HDAC inhibitors were an area of intensive research. However, the expression profiles and prognostic value of the HDACs required more elucidation.Methods: Multiple biomedical databases were incorporated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Increased immune cell infiltration levels are linked to heightened tumor aggressiveness in a range of cancers including breast cancer, kidney renal clear cell carcinoma, uveal melanoma, pancreatic cancer, and osteosarcoma [41][42][43][44][45][46][47][48]. In gliomas, including LGG, increased immune cell infiltration levels showed poor prognosis and more aggressive phenotypes [21,22,[49][50][51][52][53][54][55][56][57]. Thus, we report that low PODNL1 methylation, specifically of CpG sites cg07425555, cg26969888, cg18547299, and cg24354933, may be a key factor in the modulation of immune infiltrates in the LGG tumor microenvironment, affecting its aggressiveness and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased immune cell infiltration levels are linked to heightened tumor aggressiveness in a range of cancers including breast cancer, kidney renal clear cell carcinoma, uveal melanoma, pancreatic cancer, and osteosarcoma [41][42][43][44][45][46][47][48]. In gliomas, including LGG, increased immune cell infiltration levels showed poor prognosis and more aggressive phenotypes [21,22,[49][50][51][52][53][54][55][56][57]. Thus, we report that low PODNL1 methylation, specifically of CpG sites cg07425555, cg26969888, cg18547299, and cg24354933, may be a key factor in the modulation of immune infiltrates in the LGG tumor microenvironment, affecting its aggressiveness and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we compared the prognostic predictive abilities of 20 different risk signatures of gliomas in TCGA from published articles, including inflammatory response-related gene (IRRG) signature ( Yan et al, 2022 ), DNA damage and repair-related gene (DDRRG) signature ( Li et al, 2022c ), CXCR members signature ( He et al, 2022 ), pyroptosis-related gene signature ( Zhang M. et al, 2021b ; Chao et al, 2022 ; Yang et al, 2022 ; Zhang et al, 2022 ), ECM-related gene (ECMRG) signature ( Li et al, 2022b ), tripartite motif (TRIM) family gene signature ( Xiao et al, 2022 ), antigen presentation machinery (APM) signature ( Chen et al, 2022 ), natural killer cell-related gene (NKRG) signature ( Li C. et al, 2022a ), IL-4-related gene (IL4RG) signature ( Qi et al, 2022 ), hypoxia-related gene (HRG) signature ( Gao et al, 2021 ), S100 family-based signature ( Hu et al, 2021 ), TIME signature ( Zhang C. et al, 2021a ), focal adhesion-related gene (FARG) signature ( Li et al, 2021 ), m6A RNA methylation regulator signature ( Cong et al, 2021 ), HDAC1-related signature ( Fan et al, 2021 ), RNA-binding protein (RBP)-based signature ( Chen et al, 2021a ) and ferroptosis-related gene (FRG) signature ( Chen et al, 2021b ). The results of univariate and multivariate Cox analyses showed that our ARG signature had independent predictive ability ( p < 0.001, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that HDAC1 is overexpressed in diverse human malignancies, such as prostate cancer, breast cancer, liver cancer, and lung cancer [ 18 – 21 ]. HDAC1 is also highly expressed in glioma tissue, and high expression of glioma is associated with glioma cell proliferation, migration, invasion, angiogenesis, and a poor prognosis [ 22 ]. In addition, has been suggested that increased activation of HDAC1/2/6 and Sp1 underlies therapeutic resistance and tumor growth in glioblastoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%